1988
DOI: 10.7326/0003-4819-108-5-658
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Simple Clinical Measurements to Predict Perfusion Status after Intravenous Thrombolysis

Abstract: To determine whether coronary patency could be detected early during thrombolytic therapy, commonly used markers of perfusion were recorded in 386 patients with acute myocardial infarction treated with tissue plasminogen activator. Infarct artery angiography 90 minutes after initiation of therapy was used to determine perfusion status. Of patients with complete resolution of ST segment elevation before the angiogram, 96% (95% confidence interval, 79% to 100%) showed perfusion on the angiogram, and among those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
2

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(47 citation statements)
references
References 18 publications
0
45
0
2
Order By: Relevance
“…5 However, in several trials using these criteria, predictability of reperfusion often proved insufficient. 16 As reported by Laperche et al, 3 predictability of patency of the infarct-related artery could be enhanced by combining clinical criteria with some biochemical markers.…”
Section: Discussionmentioning
confidence: 75%
“…5 However, in several trials using these criteria, predictability of reperfusion often proved insufficient. 16 As reported by Laperche et al, 3 predictability of patency of the infarct-related artery could be enhanced by combining clinical criteria with some biochemical markers.…”
Section: Discussionmentioning
confidence: 75%
“…2 Some prior studies showed that arrhythmias, such as an accelerated idioventricular rhythm, were documented in many patients, whether reperfusion occurred or not, which suggests that development of arrhythmia is not an accurate marker for evaluating coronary patency after thrombolysis. 1,25 Although several recent studies have evaluated combined noninvasive markers with better results, 4,26,27 they are of insufficient accuracy to guide clinical decisions about rescue coronary angioplasty. 16 …”
Section: Comparison Of Mdct With Classical Noninvasive Predictors Formentioning
confidence: 99%
“…1 If the failure of reperfusion is identified early and accurately, in-hospital mortality after STEMI could be significantly reduced by implementing additional treatment, such as prompt rescue percutaneous angioplasty. 1,2 There are several noninvasive clinical predictors of failed reperfusion, such as improvement of chest pain, resolution of ST-segment elevation, washout of cardiac biomarkers and reperfusion arrhythmias; however, all of these markers have limitations for clinical decision making regarding additional invasive reperfusion therapy. [1][2][3][4] The recent introduction of the 16-slice multidetector row computed tomography (MDCT), with its high temporal resolution and increased gantry rotation, has enabled more accurate evaluation of the coronary tree.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chest pain resolution is not sufficiently accurate for decision making (33,34). Accelerated idioventricular rhythm is a relatively specific but insensitive predictor of patency (35).…”
Section: Clinical Assessment Of Reperfusionmentioning
confidence: 99%